Eccentric compression behavior of concrete-encased-and-filled steel tube columns with high-strength circular steel tube. (November 2019) - Lee, Ho-Jun; Park, Hong-Gun; Choi, In-Rak
Abstract: An experimental research was conducted for the eccentric compression behavior of concrete-encased-and-filled steel tube (CEFT) columns with high-strength circular steel tube. Five eccentrically loaded columns and one concentrically loaded column were tested under monotonic axial compression. The parameters of the test specimens included axial-load eccentricity, tie spacing, and the use of concrete encasement. In addition to conventional perimeter ties, U-cross ties were used to prevent the premature spalling of thin concrete encasement as well as local buckling of longitudinal rebars. Although early vertical cracking occurred at the compressive face, the outer concrete significantly contributed to the stiffness and strength of the composite column without the premature failure. The test strengths were compared with the predictions of current design codes, addressing contributions of the whole encasement. The CEFT specimens showed substantial ductility even after the concrete crushing, owing to the increased resistance of the high-strength circular steel tube and confined infill concrete. To verify overall behavior of the test specimens, nonlinear numerical analysis using a fiber model was performed. Highlights: Concrete-encased-and-filled steel tube (CEFT) column with thin concrete encasement proposed for large-column construction. High-strength circular steel tube utilized to enhance structural performance of the CEFT column. Detailed description and discussion of eccentric axial compression tests. Experimental behavior of the CEFT column verified by fiber model analysis.